Effect of Quilting Sutures in The Prevention of Seroma Following Ventral Hernia Repair - Sridhar, J.; Vishagan S, Abhi; Kumar, Dinesh; Premnath, Premnath; Manohar Reddy, Vangala (Journal of Neonatal Surgery, 2025)
Objective: Seroma formation is a common postoperative complication following ventral hernia repair, potentially leading to prolonged recovery, increased infection risk, and higher morbidity rates. Quilting sutures have been proposed as an effective technique to reduce dead space and promote tissue adherence, thereby minimizing seroma formation. This study aims to evaluate the effectiveness of quilting sutures in preventing seroma formation compared to the traditional closure technique. Methods: A prospective randomized controlled trial was conducted over 12 months at Vinayaka Missions Kirupananda Variyar Medical College and Hospitals, Salem. involving 50 patients undergoing ventral hernia repair. The patients were randomly assigned into two groups: Group A (n=25) underwent traditional closure, and Group B (n=25) underwent closure using quilting sutures. Postoperative outcomes, including seroma incidence, total drain output, duration of drain placement, and wound-related complications, were assessed and statistically analyzed. Results: The incidence of seroma formation was significantly lower in Group B (0%) compared to Group A (32%) (p<0.05). The total drain output was significantly lower in Group B, with a mean of ≤100 mL in 52% of patients, whereas 36% of Group A had drain output exceeding 201 mL. Additionally, the drain removal time was significantly shorter in Group B (p<0.01), with 56% of patients having their drains removed by Day 3, compared to only 16% in Group A. Conclusion: The use of quilting sutures in ventral hernia repair significantly reduces seroma formation, decreases drain output, and allows for earlier drain removal, improving overall postoperative recovery. These findings support the routine implementation of quilting sutures in ventral hernia repair to enhance patient outcomes. Further larger-scale studies with long-term follow-up are recommended to strengthen these conclusions.